How effective is the registration of sales? - Hana Zídková; Jana Tepperová (European Financial and Accounting Journal, 2017)
The registration of sales is a topical issue of the tax policy and one of the recent measures against the shadow economy and tax evasion introduced in the Czech Republic. After its implementation, first evaluations of the impact on tax revenues are being provided. Within this paper, we discuss the methodology used to provide estimates of the increase in tax revenues based on the national accounts data, estimate the increase in VAT revenues for restaurant services and compare it with previous estimates. We provide three different estimates according to the assumed proportion of VAT non-tax payers based on national accounts data. According to our results, VAT revenues would increase by approx. 2.5 bill. CZK when all restaurants become VAT payers or by approximately 1 bill. CZK if only 8 % of restaurants remain VAT non-payers. If the proportion of VAT non-payers does not change after the registration of sales, the VAT revenues would decrease by 0.45 bill. CZK due to the reduction of the tax rate.
Keywords: H2; 650; Concealed revenues; Estimates; Registration of sales; Shadow economy